Transformational Leadership and Teacher Performance as Determining Factors of ICT-Based School Quality - Wilia Ardayanti; Reva Maria Valianti; Alhadi Yan Putra (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aims to examine the effects of transformational leadership and teacher performance on ICT-based school quality, with curriculum implementation serving as a mediating variable, in junior high schools in the Empat Petulai Dangku District. The study was motivated by the predominance of administrative leadership practices, inconsistent teacher performance, and the suboptimal implementation of ICT-based curricula, which have hindered efforts to improve school quality. A quantitative survey design was employed using proportional random sampling to select the research participants. Data were analysed using multiple linear regression and path analysis to examine both direct and indirect relationships among the variables. The findings indicate that transformational leadership and teacher performance significantly and positively influence curriculum implementation as well as ICT-based school quality. Furthermore, curriculum implementation was found to mediate the relationship between transformational leadership, teacher performance, and ICT-based school quality, indicating that effective curriculum implementation strengthens the contribution of leadership and teacher performance to school improvement. These findings suggest that visionary school leadership, professional teacher performance, and effective ICT integration are essential components for enhancing school quality in the digital era. The study provides empirical evidence supporting the integration of transformational leadership, teacher performance, and curriculum implementation as key strategies for improving ICT-based school quality.